The Faust Myth Religion and the Rise of Representation - Hawkes, D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
This book traces the evolution of the Faust myth from the Sixteenth century to modern times. The authors studied include Marlowe, Calderon, Milton, Goethe, Byron, Dostoevsky, Wilde, Thomas Mann, and Salman Rushdie.
Keywords: Literature—History and criticism; European literature; Literature, Modern; Civilization—History.; Literary History; European Literature; Early Modern/Renaissance Literature; Cultural History